Appetitive and aversive visual learning in freely moving Drosophila - Schnaitmann, Christopher; Vogt, Katrin; Triphan, Tilman; Tanimoto, Hiromu (Frontiers in Behavioral Neuroscience, 2010)
To compare appetitive and aversive visual memories of the fruit fly Drosophila melanogaster, we developed a new paradigm for classical conditioning. Adult flies are trained en masse to differentially associate one of two visual conditioned stimuli (blue and green light as conditioned stimuli or CS) with an appetitive or aversive chemical substance (unconditioned stimulus or US). In a test phase, flies are given a choice between the paired and the unpaired visual stimuli. Associative memory is measured based on altered visual preference in the test. If a group of flies has, for example, received a sugar reward with green light, they show a significantly higher preference for the green stimulus during the test than another group of flies having received the same reward with blue light. We demonstrate critical parameters for the formation of visual appetitive memory, such as training repetition, order of reinforcement, starvation, and individual conditioning. Furthermore, we show that formic acid can act as an aversive chemical reinforcer, yielding weak, yet significant, aversive memory. These results provide a basis for future investigations into the cellular and molecular mechanisms underlying visual memory and perception in Drosophila.